Determinants of Sub-Sovereign Government Ratings In Europe - Nicolas JANNONE-BELLOT; Luisa MARTÍ-SELVA; Leandro GARCÍA-MENÉNDEZ (Transylvanian Review of Administrative Sciences, 2017)
The aim of this paper is to identify the determinantsof the rating assigned to sub-sovereignentities in Germany, Austria, Belgium, France,Italy and Spain, using a total of 92 territorial entitiesfor the 1989-2012 period. Multinomial orderedprobit estimation models were estimatedfor each specifi cation and agency.We conclude that the country’s rating is oneof the most important determinants of regionalgovernment’s ratings with a positive infl uence(as expected), and that the country debt/GDPratio is a stronger determinant for regions thantheir own indebtedness with a negative sign.Other relevant variables are population growthrate, unemployment rate, elderly people weight,regional public expenditure weight and size. Additionally,economic variables, such as country’srating and population growth are more importantto Fitch; whereas budget variables and size variablesare more relevant to Moody’s. Debt variablesand elderly people ratio are more importantto S&P.